Multifrequency system with multipoint and integral conditions - Bihun, Yaroslav; Petryshyn, Roman; Skutar, Ihor; Melnyk, Halyna (Acta et Commentationes Exact and Natural Sciences, Tiraspol State University, Respublica Moldova, 2021)
For the multifrequency system of equations with linear delays and multipoint and integral conditions, the existence and uniqueness of the solution in space is proved. The method of averaging over fast variables is substantiated and the error of the method is estimated, which obviously depends on the small parameter. The obtained result is illustrated by a model example.
In memoriam - Academician Mitrofan Choban
Keywords: multifrequency system, integral condition, averaging method, small parameter, resonance, error estimation, slow and fast variables.